Variability of phenolic compounds in different varieties of kale cabbage (Brassica oleracea L. var. acephala) - E. Almugrabi; I. V. Galiev; R. P. Khakimzyanova; A. A. Mostyakova; O. A. Timofeeva (Овощи России, 2024)
Relevance. Cabbage Kale (Brassica oleracea L. var. acephala) is a green, red and purple leafy vegetable cultivated in Northern and Central Europe, as well as North America. Kale deservedly occupies a high place in the list of functional products due to its high content of biologically active substances. Kale contains vitamins, minerals, antioxidant compounds, carbohydrates, unsaturated fatty acids, proteins and dietary fiber. Despite its high attractiveness as a functional food product, it is not cultivated on a massive scale in Russia.Methodology. The purpose of this work is to study the content of phenolic compounds in two varieties of kale cabbage to substantiate recommendations for its cultivation in Russia. The variety and hybrid of kale cabbage – Dwarf Blue Scotch with green leaves and the hybrid Redbor F1 with red leaves – were used as the object of the study. The content of soluble phenolic compounds and flavonoids, as well as the qualitative composition of phenolic compounds in kale cabbage, was studied. Determination was carried out according to generally accepted methods. Grown plants at the age of 16 weeks were used as samples for analysis. The experiment was carried out in laboratory conditions in 5 replicates.Results. The results of the studies indicate a fairly high content of phenolic compounds and flavonoids in the studied varieties of kale cabbage. It has been demonstrated that the Redbor F1 hybrid is characterized by a higher content of soluble phenolic compounds compared to the Dwarf Blue Scotch variety by an average of ~20%. It was concluded that this Redbor F1 hybrid can be used to develop methods for increasing the efficiency of the synthesis of secondary metabolites that are beneficial to human health, and is recommended to farmers for cultivation in the Russian Federation.